Decoding past microbial life and antibiotic resistance in İnonü Cave's archaeological soil. - Sukran Ozturk; F Gülden Ekmen; Hamza Ekmen; Esra Mine Ünal; Ayşegül Er; Emre Keskin; Benjamin Stanley Arbuckle (PLoS ONE)
This study, which bridges the disciplines of archaeology and microbiology, examines the ancient bacterial communities and antibiotic-resistance genes in soil samples collected from İnönü Cave in Zonguldak, Turkiye. Our aim is to provide a comprehensive understanding of historical human activities and their influence on microbial communities. Soil samples were gathered from four distinct cultural levels from the Chalcolithic Age to the Early Iron Age. The microbial communities were characterized, and antibiotic-resistance genes were identified using high-throughput sequencing of 16S rRNA genes and metagenomic studies. This interdisciplinary approach not only enriches our understanding of ancient microbial communities but also opens up new avenues for research and collaboration. The results of our study showed a wide range of microorganisms, including prominent bacterial groups such as Acidobacteriota, Actinobacteriota, Bacteroidota, Chloroflexi, Cyanobacteria, Firmicutes, Myxococcota, and Proteobacteria. The study identified the presence of the tetracycline resistance gene tetA in Chalcolithic samples, the class 1 integron intl1 in Early Bronze Age samples, and the oxacillinase gene OXA58 in Late Bronze Age samples. These findings underscore the long-term impact of human activities on microbial communities, as antibiotic-resistance genes have been present and have remained over various historical periods, perhaps influenced by both human activities and environmental variables. This knowledge is crucial for understanding the resilience and adaptability of microbial communities in the face of human-induced changes. The coexistence of these resistance genes and alterations in the microbial population suggest substantial connections between human activities and soil microbiota. This study, which draws on the fields of archaeology, microbiology, and environmental science, offers valuable insights into the ancient microbial ecology and underscores the enduring presence of antibiotic resistance. It emphasizes the necessity of a comprehensive, interdisciplinary approach, spanning multiple fields, to comprehend microbial communities' evolution and resistance mechanisms in archaeological settings.